2014
DOI: 10.1016/j.cma.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Quasicontinuum-based multiscale approaches for plate-like beam lattices experiencing in-plane and out-of-plane deformation

Abstract: The quasicontinuum (QC) method is a multiscale approach that aims to reduce the computational cost of discrete lattice computations. The method incorporates smallscale local lattice phenomena (e.g. a single lattice defect) in macroscale simulations. Since the method works directly and only on the beam lattice, QC frameworks do not require the construction and calibration of an accompanying continuum model (e.g. a cosserat/micropolar description). Furthermore, no coupling procedures are required between the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…A simple remedy to avoid this numerical issue, also exploited in this contribution, is to use relatively large triangles in the coarse-grained domain and couple them kinematically in a non-conforming manner to the fully resolved lattice model in the domain of interest [28]. Hence, in this work no transition regime is present at all.…”
Section: Interpolationmentioning
confidence: 99%
See 4 more Smart Citations
“…A simple remedy to avoid this numerical issue, also exploited in this contribution, is to use relatively large triangles in the coarse-grained domain and couple them kinematically in a non-conforming manner to the fully resolved lattice model in the domain of interest [28]. Hence, in this work no transition regime is present at all.…”
Section: Interpolationmentioning
confidence: 99%
“…In [28] it was observed that the triangles in the transition zone in QC approaches with higher-order interpolation have too many triangle nodes, i.e. too many degrees of freedom, than are governed by underlying lattice.…”
Section: Interpolationmentioning
confidence: 99%
See 3 more Smart Citations